Chronicle of a Pandemic Foretold - Bizzarri, Mariano (Organisms. Journal of Biological Sciences, 2020)
Citation: Bizzarri, B, 2020, “Chronicle of a Pandemic Foretold”, Organisms: Journal of Biological Sciences, vol. 4, no. 1, pp. 102-112. DOI: 10.13133/2532-5876/16966.